The effects of plasma to red blood cells transfusion ratio on in-hospital mortality in patients with acute type A aortic dissection - Yao, Run; Yan, Danyang; Fu, Xiangjie; Deng, Ying; Xie, Xi; Li, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background: Blood transfusion is a frequent and necessary practice in acute type A aortic dissection (AAAD) patients, but the effect of plasma/red blood cells (RBCs) ratio on mortality remains unclear. The aim of this study is to investigate the association between plasma/RBCs transfusion ratio and in-hospital mortality in patients with AAAD. Methods: Patients were admitted to Xiangya Hospital of Central South University from January 1, 2016 to December 31, 2021. Clinical parameters were recorded. Multivariate Cox regression model was used to analyze the association between transfusion and in-hospital mortality. We used the smooth curve fitting and segmented regression model to assess the threshold effect between plasma/RBCs transfusion ratio and in-hospital mortality in patients with AAAD. Results: The volumes of RBCs (14.00 [10.12-20.50] unit) and plasma (19.25 [14.72-28.15] unit) transfused in non-survivors were significantly higher than in survivors (RBCs: 8.00 [5.50-12.00]) unit; plasma: 10.35 [6.50-15.22] unit). Multivariate Cox regression analysis showed plasma transfusion was independent risk factor of in-hospital mortality. Adjusted HR was 1.03 (95% CI: 0.96-1.11) for RBCs transfusion and 1.08 (95% CI: 1.03-1.13) for plasma transfusion. In the spline smoothing plot, mortality risk increased with plasma/RBCs transfusion ratio leveling up to the turning point 1. Optimal plasma/RBCs transfusion ratio with least mortality risk was 1. When the plasma/RBCs ratio was <1 (adjusted HR per 0.1 ratio: 0.28, 95% CI per 0.1 ratio: 0.17-0.45), mortality risk decreased with the increase of ratio. When the plasma/RBCs ratio was 1-1.5 (adjusted HR per 0.1 ratio: 2.73, 95% CI per 0.1 ratio:1.13-6.62), mortality risk increased rapidly with the increase of ratio. When the plasma/RBCs ratio was >1.5 (adjusted HR per 0.1 ratio: 1.09, 95% CI per 0.1 ratio:0.97-1.23), mortality risk tended to reach saturation, and increased non-significantly with the increase of ratio. Conclusion: A 1:1 plasma/RBCs ratio was associated with the lowest mortality in the patients with AAAD. And non-linear relationship existed between plasma/RBCs ratio and mortality.